Detection of Lahar Flow Direction from Semeru Eruption on 4 December 2021 using Gravity Method - Arie Realita; Muhammad Nurul Fahmi; Tjipto Prastowo; Madlazim Madlazim (JPSE (Journal of Physical Science and Engineering), 2022)
Mount Semeru, an active, steep-sided volcano in East Java, erupted on 4 December 2021 following extreme rainfall that led to an avalanche of hot pyroclastic flows and lahars. Besides a debatable eruption source with no preceding seismic signals observed, it has drawn the international community's attention for its extent of largely impacted areas down the summit. In this study, we used gravity method modeling of the local anomaly in density distribution after the event to determine the unique pattern of the lahar flow direction with the corresponding extent and the spread of the flow. The data were collected from a TOPEX satellite altimeter and processed using a number of specific techniques to obtain a contoured map of local anomaly. The results showed that the main path of the flow was found to descend down the slope to the southeast of the crater, extending to a distance of about 20 km with a maximum lahar flow width of about 2 km toward agricultural lands and populated areas, consistent with the high-resolution satellite imagery produced by UNOSAT-UNITAR. It suggests that gravity anomaly could be used to simulate the flow pattern and the widespread damage of volcanic materials after an eruption.DOI: 10.17977/um024v7i22022p075